The European Parliament and the Layered Politicization of the External Dimension of the Common Fisheries Policy - Zimmermann, Hubert (2019)
When the Lisbon Treaty entered into effect, the European Parliament became a core player in the decision-making processes of the EU’s Common Fisheries Policy (CFP) and its external dimensions. This new role suggested a shift towards stronger politicization in what had previously been a rather technocratic policy field. However, the CFP is not yet marked by a clear and consistent level of politicization. I use the concept of ‘layered politicization’ to explain this pattern. Although it is not comparable to the degree of political controversy shaping fully politicized policy fields, some similar political dynamics can be observed. Among them is a transformation in the policy process due to higher ratification requirements; a higher likelihood of political deadlock resulting from an increasing number of veto-players; and a strengthening of the contested legitimacy of EU decision-making. An empirical test of these theoretical propositions is provided here in the form of two case studies; the negotiation of Fisheries Partnership Agreements with Morocco and Mauritania.